2016
DOI: 10.1507/endocrj.ej16-0242
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of adrenal insufficiency including adrenal crisis: a Japan Endocrine Society clinical practice guideline [Opinion]

Abstract: Abstract. This clinical practice guideline of the diagnosis and treatment of adrenal insufficiency (AI) including adrenal crisis was produced on behalf of the Japan Endocrine Society. This evidence-based guideline was developed by a committee including all authors, and was reviewed by a subcommittee of the Japan Endocrine Society. The Japanese version has already been published, and the essential points have been summarized in this English language version. We recommend diagnostic tests, including measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 98 publications
1
101
0
Order By: Relevance
“…While a rapid ACTH test should have been carried out for a definitive diagnosis (29), the duration from the onset of symptoms to the diagnosis was extremely long; thus, diagnostic treatment was prioritized. The endocrine system tests revealed that among the anterior pituitary hormones, only the levels of ACTH were lower than normal, with the levels of other anterior pituitary hormones, such as PRL, LH, FS and TSH, being higher than normal; furthermore, the cortisol levels were also lower than normal.…”
Section: Discussionmentioning
confidence: 99%
“…While a rapid ACTH test should have been carried out for a definitive diagnosis (29), the duration from the onset of symptoms to the diagnosis was extremely long; thus, diagnostic treatment was prioritized. The endocrine system tests revealed that among the anterior pituitary hormones, only the levels of ACTH were lower than normal, with the levels of other anterior pituitary hormones, such as PRL, LH, FS and TSH, being higher than normal; furthermore, the cortisol levels were also lower than normal.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal insufficiency is possible, if basal cortisol is <3 to 4 μg/dL or post stimulation cortisol is <18 μg/dL. [17] …”
Section: Discussionmentioning
confidence: 99%
“…However, serum ACTH level induced by 250 μg ACTH administration is 1000 to 60,000 pg/dL, higher over the physiological concentration. [1719] …”
Section: Discussionmentioning
confidence: 99%
“…The replacement period has been reported to be average 1 year and 8 months. In the case of SCS, the same protocol is recommended, but the replacement period may be shorter than that of CS because of the relatively weaker suppression of hypothalamic-pituitary adrenal (HPA) axis [35].…”
Section: Treatment Guidelines For Scsmentioning
confidence: 99%